PROBLEMS OF INFORMATICS AS COMPREHENSIVE BASIC SUBJECT - B.V. SOBOL; E.V. RASHIDOVA (Advanced Engineering Research, 2021)
The main questions of specialists training in the field of information technologies are considered. The place of Informatics in the cycle of common mathematical and nature science subjects is determined. Analysis of studying plans of nature science cycle for specialties where Informatics is not a dominating subject is fulfilled.